Pengaruh Kebijakan Dividen, Profitabilitas, Dan Pertumbuhan Perusahaan Terhadap Kebijakan Hutang Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia (Bei) - Ita Rahmawati; Lailatus Sa'adah; Zakiyatul Miskiyah (Journal of Financial and Tax, 2024)
The goal of this study was to ascertain how the debt policies of banking businesses listed on the Indonesia Stock Exchange would evolve between 2018 and 2022 depending on the dividend policy, profitability, and company growth. The dividend policy, profitability, and corporate growth on the company's debt policy are the variables used in this study. Purposive sampling, or selecting participants based on predetermined criteria, was the sampling technique utilized in this study. Four companies served as samples for this study's criteria. Panel data regression analysis is the method used to determine the combined and individual effects of the independent factors on the dependent variable. Data analysis or regression results demonstrate that debt policy is simultaneously impacted by dividend policy, profitability, and firm growth. Partially, the factors affecting the dividend policy, profitability, and corporate expansion have no appreciable impact on the debt policy. The adjusted R square value of the coefficient of determination is 0.937112 in magnitude. This indicates that three independent variables may account for 93.7112% of the dependent variable, or debt policy, while additional variables or factors outside the model can account for the remaining 6.2888% of the dependent variable